Panel Analysis of Wholesale Profitability in the Republic of Serbia - Stojanka Dakić; Daniela Nuševa; Sonja Vučenović; Mirjana Hladika; Lenče Petreska; Dejan Jovanović (Anali Ekonomskog fakulteta u Subotici, 2025)
Purpose: The aim of this paper is to analyze the profitability of wholesale companies in the Republic of Serbia and to investigate the factors that influence it.Мethodology: Profitability is measured by return on assets (ROA), while the impact of independent factors such as quick ratio, leverage, inventory turnover period, assets turnover ratio, growth, and company size is analyzed through panel regression. The sample includes 18 wholesale companies from the Republic of Serbia, whose financial statements were observed during the period from 2007 to 2023.Findings: During this period, companies included in the sample showed a trend of profitability growth. The average return on assets was 6.69%, which means that wholesale companies, on average, generated 6.69 EUR of net profit for every 100 EUR invested in assets. The results of the panel regression analysis show that leverage and inventory turnover period have a significant negative impact on profitability. On the other hand, asset turnover ratio, growth, and company size have a positive and significant impact on profitability.Originality/value: This paper contributes to the theoretical and practical research of the factors of profitability, especially from the perspective of wholesale companies in the Republic of Serbia.Practical implications – The results of this research are both theoretically and practically significant for the process of making reliable decisions in managing profitability and can be useful for various stakeholders such as owners and/or managers of wholesale companies, regulatory bodies, and others.Limitations: The limitation of this research is that it is focused only on the wholesale sector in the Republic of Serbia, and future research could include other countries to investigate economic specificities and their impact on profitability.